2013
DOI: 10.1590/s0102-09352013000500027
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho produtivo e econômico do confinamento de bovinos zebuínos alimentados com três dietas de alto concentrado

Abstract: RESUMOEstudaram-se o desempenho produtivo e a viabilidade econômica no confinamento de 24 bovinos, inteiros, com idade média de 23 meses, sendo 12 Nelore (NEL) e 12 F1 Nelore x Brahman (NBR), divididos em três dietas: SIL  silagem de milho e ração concentrada; PEL  exclusiva de pellets; GRN  milho grão inteiro e pellets. O experimento foi realizado em um delineamento inteiramente ao acaso, em esquema fatorial 2x3, com quatro repetições. Os animais NBR apresentaram resultados semelhantes aos da raça NEL quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
11

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 9 publications
1
3
0
11
Order By: Relevance
“…The average daily gain in live weight of the whole corn grain-based diet was different (P<0.05) from that of the other treatments (Table 2), which is partially explained by the lower final weight and carcass weight than in the animals fed steam-flaked corn-and ground cornbased diets. Mandarino et al (2013) reported ADG and dry matter daily intake of 1.25 kg and 8.52 kg (1.79% LW), respectively, when studying Nellore and Nellore × Brahman animals given a whole corn grain-based diet (corn grain:pellet ratio -85:15%), with 482.14 kg live weight at slaughter and a 96-day feedlot period, which are similar results to those obtained in this study. These results suggest that whole corn grain-based diets may be recommended for finishing Bos indicus animals, with similar gains to those obtained in the present study.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The average daily gain in live weight of the whole corn grain-based diet was different (P<0.05) from that of the other treatments (Table 2), which is partially explained by the lower final weight and carcass weight than in the animals fed steam-flaked corn-and ground cornbased diets. Mandarino et al (2013) reported ADG and dry matter daily intake of 1.25 kg and 8.52 kg (1.79% LW), respectively, when studying Nellore and Nellore × Brahman animals given a whole corn grain-based diet (corn grain:pellet ratio -85:15%), with 482.14 kg live weight at slaughter and a 96-day feedlot period, which are similar results to those obtained in this study. These results suggest that whole corn grain-based diets may be recommended for finishing Bos indicus animals, with similar gains to those obtained in the present study.…”
Section: Resultssupporting
confidence: 87%
“…Diets with whole corn grain and pelleted supplement have been used in recently Brazil and provided satisfactory animal performance, but the carcass and meat quality was not assessed (Mandarino et al, 2013). The objective of this experiment was to evaluate the effect of different energy sources in the diet on carcass and meat quality of Nellore bulls.…”
Section: Introductionmentioning
confidence: 99%
“…Bourg et al (2012) obtiveram resultados semelhantes aos do presente trabalho, ao utilizar ULL em três dietas para novilhos Angus mestiços, com diferentes fontes de proteína; contudo, estes autores não constataram diferenças (p>0,10) para GMD, PF e CMS. Mandarino et al (2013) avaliaram bovinos Nelore e Nelore × Brahman submetidos a três diferentes tratamentos, com dietas de alto concentrado: 25% de silagem de milho + 75% de concentrado; exclusiva de pellets; e 85% de milho grão inteiro + 15% de pellets. Os autores obtiveram valor semelhante aos do presente trabalho para CMS (9,75 kg por dia), porém um valor menor para CMS%PV (1,99), uma vez que os animais apresentaram maior PF (493,32 kg).…”
Section: Resultsunclassified
“…According to Pacheco et al (2013), carcass weight is a very important characteristic for the producer, other than the degree of finishing and animal age, being directly related to income. Mandarino et al (2013) evaluated the productive characteristics of cattle fed diets that used 75% of concentrate or were based exclusively (100%) on concentrate, and verified differences in warm carcass weights between the different food treatments -a fact these authors also associated with the difference in animal weight gain. Regarding yields of warm and cold carcasses, the highest yields were observed in corn-fed animals, followed by those maintained on a rice diet, and finally cattle fed white oats.…”
Section: Resultsmentioning
confidence: 89%